PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PADA CV SINCO JAYA ABADI PEMATANGSIANTAR - Winny Listyarini; Darwin Lie; Efendi Efendi; Sisca Sisca (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2018)
The result of this research: 1.Compensation and work environment is good and the job satisfaction is already categorized as satisfied. 2. The results of multiple regression analysis is: Ŷ=7,358 + 0,756X1 + 0,532X2, meaning that there is positive influence between compensation and work environment on job satisfaction. 3. Analysis coefficient is r = 0,790, which means there is moderately high and positive correlation between compensation and work environment with the job satisfaction.The value of the coefficient of determination (KD) 0,624, meaning that the level of job satisfaction can be explained 62,4% by compensation and work environment. 4. Hypothesis test result stated that H0 is rejected, it means compensation and work environment have positive and significant influence to job satisfaction at CV Sinco Jaya Abadi Pematangsiantar either simultaneously or partially.The suggestion of this research for financial compensation, the company can provide holiday allowance according to the length of service period of the employee. For increase comfort in office room, company can add an air conditioning. For non physical work environment to resolve relationship issues with colleagues, the colleagues need to listen to opinions and advice provided by colleagues. Meanwhile, to improve job satisfaction the company needs to hold an event that involves all employees so that they can interact with each other. Keywords: Compensation,Work Environment, and Job Satisfaction.